A New Optimization CAD/CAM/CAE Technique for the Processing of the Complex 3D Surfaces on 5 Axes CNC Machines. (2015) - Wagner, Erika
Abstract: In the case of complex surfaces, the processing on 5 axes CNC machines may be approached by taking into consideration the fact that the axis of the cutting tool must stand in a normal direction towards the plan of the surface that needs processing. In this case, a data file will be used, which will be transferred to an application which is capable of generating the CNC code that can be recognized by the programming language of the machine. At the same time, in order to optimize this procedure, the processing of the 3D solid surfaces may be approached. In this case, the piece which is considered a solid, may be decomposed into successive sections that will optimally be processed on the 5 axes CNC machine using the facilities of the 5 axes CNC machine. One viable solution that can be applied in the case of the processing of the 3D surfaces is the decomposition of a solid into successive sections, according to the processing plan. If we use the procedure above described for the processing of the 3D complex surfaces, essential benefits will occur, related to the conditions of the processing, using a cutting tool on a 5 axes CNC machine, especially as compared to the 3 axes CNC machine. In the case of the processing procedure of a 3D complex surface held on a 3 axes CNC machine, risks may appear, such as obtaining a surface with form errors caused by inappropriate position of the cutting tool towards the generated outline. This inconvenient may be eliminated when using a 5 axes CNC machine. This procedure is the subject of the study presented in this article.